Prevalence of pulmonary function abnormalities in type 2 diabetes mellitus and its association with HbA1c in nonsmokers - Sarkar, Suman; Roy, Nirmalya; Barman, Souvik (International Journal of Advances in Medicine, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder with vast social and economic consequences an ageing population and obesity due to sedentary lifestyle are one of the foremost reasons for the development of type 2 diabetes mellitus. Aim of the current study was to ascertain the burden of respiratory function abnormalities in type 2 diabetic subjects and its correlation with symptom and hba1c in non-smokers. Methods: This cross-sectional study was conducted in KPC medical college, Jadavpur. Patients of type 2 diabetes mellitus between the age of 30-80 years fulfilling the modified Borg dyspnoea scale were included after excluding heart failure, COPD, musculoskeletal disorders. The selected subjects were then subjected to a PFT with reversibility and DLCO assessment Pattern of PFT abnormality recorded. Total of 65 subjects were chosen for the study. Results: In our study most of the patients had Restrictive abnormality Female 24 (42.9%) and male 32 (57.1%). Rest 3 (50.0%) Female patients and 3 (50.0%) male patients had Mixed abnormality. 2 (66.7%) female patients and 1 (33.3%) male patient had normal abnormality which was not statistically significant (p=0.6939). Conclusions: Pulmonary function is reduced in type 2 diabetes. Diabetes duration seems a more important influence than glycaemic control, but the definitive direction as well as the exact pathophysiological mechanism to explain this association requires further investigation.